Fuzzy Logic Analysis of Flood Disaster Monitoring and Assessment of Damage in SE Anatolia Turkey - Bayraktar, Hueseyin; Bayram, Buelent (IEEE, 2009)
Southeast Anatolia Region was subject to a large flood disaster whose severity is expected only once each 100 years in November 2006. Several people died or injured after a very heavy rain fell which outlast nearly 3 hours. Nonetheless government made a strong effort to interfere the casualties. Before and after images of TERRA/ASTER satellite were used to analyse the effects of the disaster. Before image was gathered on May and after image was gathered on November. November image was registered onto May image with a very accurate rectification process in spite of a huge seasonal difference. Land use and land cover classification using an object oriented method has been performed on the study area. VNIR, SWIR and TIR bands of both satellite images were included in classification process. Fuzzy image segmentation was attempted using scale parameters of 5, 10, 20 and 30 on both images. Pre-flood and post-flood classification results were fulfilled according to the scale parameter of 5. Even though the date of the post-flood image 4 days after the flood, affected regions were determined by courtesy of object oriented fuzzy classification process.
Keywords: Flood disaster monitoring; Fuzzy logic; Object oriented classification; ASTER; Engineering